Strategy for Improving SMAW Welding Practice Learning: Case Study at Vocational High School - Syauqi, Khusni; Ardian, Aan; Sugiyono, Sugiyono (Journal of Vocational Education Studies, 2025)
Welding is one of the most essential competencies in the metal fabrication industry. Therefore, effective SMAW (Shielded Metal Arc Welding) practice learning strategies are critical to ensuring quality learning outcomes. In vocational high schools (VHS), however, challenges persist, such as low student performance, joint defects, and a lack of industry-relevant learning models. These issues underscore the need for a more in-depth examination of practical learning strategies and efforts to enhance student competencies, an area that remains underexplored. This study aims to explore strategies for improving SMAW practice learning through a single-case study conducted in a vocational high school (VHS). Data were collected via in-depth interviews with six welding teachers and four certified student welders, supported by document analysis. The findings indicate that three main strategies are essential: (1) understanding and application of welding parameters by students, (2) intensive mentoring from teachers, and (3) independent evaluation by students. These strategies have the potential to enhance both understanding and performance in SMAW practical learning in vocational settings.